If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2(3z + 1) + -8 = 48 Reorder the terms: 2(1 + 3z) + -8 = 48 (1 * 2 + 3z * 2) + -8 = 48 (2 + 6z) + -8 = 48 Reorder the terms: 2 + -8 + 6z = 48 Combine like terms: 2 + -8 = -6 -6 + 6z = 48 Solving -6 + 6z = 48 Solving for variable 'z'. Move all terms containing z to the left, all other terms to the right. Add '6' to each side of the equation. -6 + 6 + 6z = 48 + 6 Combine like terms: -6 + 6 = 0 0 + 6z = 48 + 6 6z = 48 + 6 Combine like terms: 48 + 6 = 54 6z = 54 Divide each side by '6'. z = 9 Simplifying z = 9
| 8-5(z+2)=-2(5z-2)-2 | | 2x+11+x+7=18 | | n+3.1n-4.7=3.6(n-4.5) | | 0.168x=0.2x+0.667 | | 3(x+3)-6x=2(4-2x) | | -145=7r+2(7r+1) | | 6(x-5)=4(2x-1) | | 3x+9=44-2y | | M*0= | | -2.7u+5.3=-1.4u-2.5 | | 2/3/87 | | 3w-(6+w)=12 | | 17=2k+8+k | | 90(2/5) | | 6(x+3)=3(8+4x)-6x | | V/-50=30 | | 2x+4/3x=290 | | -5(-3x-3)=60 | | -4k-4(8k-1)=148 | | 2/3x+1/4x=x-3.75 | | .33+2z=-5/6 | | 2n+10=5n-5 | | 90(-2/5) | | -2(x-3)+3x=12 | | 0.25x-7=0.375x | | 2n+8=15 | | 2/5=18/x+3 | | -4z-2=2z+16 | | 5x-8=-5+5x-3 | | (5x-3)+(x-9)=5x | | x2/3+x+x2/3+x=290 | | H-4overj=k |